Engaging Erik Olin Wright: connecting class analysis and real utopias - Burawoy, Michael; Seidman, G. (London, UK; New York, USA: Verso, 2024)
"When the renowned social scientist Erik Olin Wright passed away in 2019, he left behind an inspirational project in process-the articulation of class and utopia. Applying Wright's core ideas to empirical material from around the world, the essays in this volume pay tribute to his generative theory, his crystalline teaching, and his personal warmth"--
Includes bibliographical references.
Keywords: Wright, Erik Olin; Marxian school of sociology; Marxist